Effect of external electric field applied to bilayer graphene bandgap: Density Functional Theory Study - Linggawati, Amilia; Arifin, Khuzaimah; Yunus, Rozan M. (International Journal of Integrated Engineering, 2022)
Graphene is a prominent material in a wide range of applications, however, the gapless nature of graphene limits its great performance in certain applications, such as in optoelectronic and photocatalytic applications field. Opening the bandgap has become one of the focused studies on graphene material today. Here, we used density functional theory (DFT) calculation to investigate the bandgap opening of bilayer graphene by external electric field applying. The calculation was performed on hexagonal stacked bilayer graphene structure using three different approximations and functional DFT; that is generalized gradient approximation (GGA) PBE and PW-91, as well as Local-density approximations (LDA) -CAPZ. The external electric field varied from 0.0 to 0.5 eV/Å/e in various electric field directions. The calculations results show that the external E-F applied in a perpendicular direction open the bandgap almost 4-times than non-determined the electric field direction. The bandgap opening by LDA functional calculation perform a smaller bandgap opening compared to GGA calculation results, while the PBE and PW-91 of GGA produced similar values at low electric field applied. The larger bandgap of 0.80 eV obtained at 0.3 eV/Å/e electric field applied calculated with both GGA functional At 0.5 eV/Å/e electric field applied, bandgap with GGA-PBE almost zero, and the crystal structure changed from cubic to triclinic with layer position become apart.